2018
DOI: 10.1111/jopr.12942
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Adhesion of Candida albicans on CAD/CAM PMMA‐Based Polymers

Abstract: CAD/CAM PMMA-based polymers may be preferable to reduce Candida-associated denture stomatitis in long-term use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(106 citation statements)
references
References 44 publications
(98 reference statements)
4
81
1
Order By: Relevance
“…Likewise, enhanced surface characteristics of CAD/CAM PMMA might be attributed to the unique manufacturing process of these materials; reduced levels of residual monomers as well as the polymerization method involved in PMMA manufacturing were previously reported to contribute to surface roughness alteration . The results of this study support Murat et al's results of lower R a values for the CAD/CAM PMMA group using a contact type profilometer and the results of Steinmassl et al, who tested different complete dentures of variable CAD/CAM PMMA brands and compared them to conventional dentures and reported significant lower roughness values for the CAD/CAM groups.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Likewise, enhanced surface characteristics of CAD/CAM PMMA might be attributed to the unique manufacturing process of these materials; reduced levels of residual monomers as well as the polymerization method involved in PMMA manufacturing were previously reported to contribute to surface roughness alteration . The results of this study support Murat et al's results of lower R a values for the CAD/CAM PMMA group using a contact type profilometer and the results of Steinmassl et al, who tested different complete dentures of variable CAD/CAM PMMA brands and compared them to conventional dentures and reported significant lower roughness values for the CAD/CAM groups.…”
Section: Discussionsupporting
confidence: 85%
“…All contact angles obtained in this study were in line with the results of the aforementioned study. Murat et al reported a higher contact angle, and consequently, higher hydrophobicity of conventional heat‐cured PMMA when compared to CAD/CAM PMMA. The results they obtained were attributed to the effect of thermal cycling.…”
Section: Discussionmentioning
confidence: 99%
“…The CAD/CAM technologies are used for the fabrication of various ceramic restorations, including inlays, onlays, crowns, and fixed partial dentures [ 202 ]. More recently, several researchers [ 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 ] investigated the use of CAD/CAM technologies for the fabrication of PMMA dental prostheses and compared the materials’ properties and various aspects of the conventional and CAD/CAM PMMA materials. In contrast to the conventional “flask–pack–press” technique, CAD/CAM techniques commonly use rapid prototyping and milling techniques [ 208 , 210 ].…”
Section: Applications Of Pmmamentioning
confidence: 99%
“…Interestingly, the adherence of fungal Candida albicans was remarkably reduced in CAD/CAM dentures [ 207 ], resulting in enhanced hydrophobicity and surface properties [ 205 , 206 , 207 ]. The increased hydrophobicity inhibits plaque accumulation on the polymer surface [ 213 , 214 ].…”
Section: Applications Of Pmmamentioning
confidence: 99%
“…Additional information about the position of the regions of interest can PMMA has a permeability to gas neglectable compared to other polymers usually used in microfluidic forms, i.e., PDMS [55]. The mean contact angle of conventional PMMA is almost 75 • , this means that it is weakly hydrophilic [56]. As explained in Section 2.7, a priming of the waste reservoir with 200 µL of culture medium is preferred to overcome hydrophobic forces.…”
Section: Device Experimental Characterization and Validationmentioning
confidence: 99%